ABSORB bioresorbable vascular scaffold vs. everolimus-eluting metallic stent in ST-segment elevation myocardial infarction (BVS EXAMINATION study): 2-Year results from a propensity score matched comparison - Brugaletta, Salvatore (ELSEVIER IRELAND LTD, 2021)
10.1016/j.ijcard.2016.04.016